Determinants Influencing the Consumption of Iron-Rich Foods among Senegalese Young Children: A Path Analysis - Dupuis, J.B.; Ndiaye, A. Ndene; Lo, N. Ba; Thiam, E.H.M.; Sall, M.; Blaney, S. (International Journal of Child Health and Nutrition, 2024)
Background: Anaemia is a public health concern among Senegalese children aged 6-59 months old. One of the potential causes of this situation is the low consumption of iron-rich foods (IRF). Understanding factors that influence the provision of IRF among young children could help prevent and control anemia. Using the extended version of the theory of planned behavior (eTPB), this nationwide study examines psychosocial and environmental determinants of the consumption of IRF in children aged 6-23 months. Methods and Materials: To this end, an existing questionnaire used for the same purpose was reviewed and re-validated. Using data collected among 418 children's caregivers on each construct of the eTPB, pathways by which individual and environmental constructs may influence the daily IRF consumption were identified. Data on IRF consumption were collected using a food frequency questionnaire. Results: Overall, 42% of children consumed IRF, while 95% of caregivers intended to provide them with IRF daily. There was no association between the intention and the actual behavior. The daily IRF consumption was instead predicted by the child's age and environmental factors. In turn, the subjective norm and the perceived behavioral control predicted the intention. Conclusion: By using a valid and reliable tool to collect data on individual and environmental factors affecting the consumption of IRF among Senegalese young children on a national scale, our research highlights potential barriers to their provision. These barriers should be considered in the design and implementation of effective interventions to improve their nutrition.